Early remdesivir to prevent severe COVID-19 in recipients of solid organ transplant: a real-life study from Northern Italy. (August 2022) - Colaneri, Marta; Amarasinghe, Nicolò; Rezzonico, Leonardo; Pieri, Teresa Chiara; Segalini, Emilio; Sambo, Margherita; Roda, Silvia; Meloni, Federica; Gregorini, Marilena; Rampino, Teresa; Pelenghi, Stefano; Ricciardi, Alessandra; et al.
Highlights (for review): Pre-emptive 3-day course remdesivir might reduce hospitalization due to COVID-19 Data on the effectiveness of this strategy in patients with COVID-19 who received solid organ transplant are lacking Patients receiving solid organ transplant who received and did not receive pre-emptive remdesivir were evaluated 28-day hospitalization due to COVID-19 was the primary outcome Remdesivir was effective in reducing hospitalization among patients with COVID-19 who received solid organ transplant Abstract: Objectives: The effectiveness of a 3-day course of remdesivir to prevent severe disease in patients with COVID-19 who received solid organ transplant (SOT) is unknown. We wanted to study the efficacy of this therapeutic option in patients with COVID-19 who received SOT in preventing both hospitalizations for outpatients and clinical worsening due to COVID-19 for those already hospitalized for other reasons. Methods: This is a single-center, retrospective, observational study conducted in the Fondazione IRCSS Policlinico San Matteo of Pavia, Northern Italy. We extracted all the data of patients with COVID-19 receiving SOT who received and did not receive pre-emptive remdesivir between December 23, 2021, and February 26, 2022. We used a Cox proportional hazard model to assess whether receiving pre-emptive remdesivir was associated with lower rates of hospitalization. Results: A total of 24 patients who received SOT were identified. Among these, seven patients (29, 1%) received pre-emptive remdesivir, whereas 17 (70, 9%) patients did not. Receiving remdesivir significantly reduced the hospitalization rate in outpatients who received SOT and the clinical worsening of the condition of already hospitalized patients who received SOT (hazard ratio 0.05; confidence interval [0.00–0.65], P -value = 0.01). Conclusion: In our cohort of patients infected with SARS-CoV-2 who received SOT, pre-emptive remdesivir was effective in reducing the hospitalization rate due to COVID-19 and in preventing the clinical worsening of the condition of patients who received SOT who were hospitalized for reasons other than COVID-19.